Synthesis and phase evolution of electrospun antiferroelectric lead zirconate (PbZrO3) nanofibers - Nawanil, Chanisa; Boomchom, Banjong; Prachayawarakorn, Jutarat; Vittayakorn, Wanwilai C.; Vittayakorn, Naratip (My University, 2012)
Lead zirconate (PbZrO3; PZO) fibers were synthesized by the electrospinning method using a solution that contained 5 wt% poly(ethylene oxide) (PEO) in ethanol and a sol-gel solution of PZO. Some parameters varied, for example, the ratio between PEO and PZO, concentrations of the precursor solution, flow rate, and calcination temperature. The as-spun and calcined PZO/PEO composite fibers were characterized by TG-DTA, X-ray diffraction, FT-IR, SEM and TEM. PZO fibers were obtained successfully with a well-developed perovskite structure after as-spun PZO/PEO composite fibers were calcined using the PZO/PEO volume ratio of 10:3 at a PZO concentration of 1.0 M at 650 °C for 4 h. Stable nanofibers were produced with an average diameter of 300 ± 64 nm. Additionally, the PZO fibers showed a Curie temperature that rose by nearly 13 °C, when comparing with a normal PZO particle. © 2012 Elsevier B.V. All rights reserved.
Keywords: Electrospinning; Lead zirconate; Sol-gel